(untitled) (PANGEEA, 2025)
Valea lui Stan (Brezoi) and Costeşti (Horezu) are both shear-zone related gold mineralizations within the metamorphic rocks in South Carpathians. They are similar in respect to the mineral associations and structural setting, but are different in respect to the geochemical parageneses and the related protores. In both occurrences the gold is present as inclusions in different sulphides (arsenopyrite, chalcopyrite, pyrite, sphalerite, pyrrhotite) and quartz. Gold occurs in these minerals at different size scales. Rarely found at macroscopic scale, gold is usually present at microscopic and submicroscopic scale, as micro-, infra- and nano-inclusions. In the two mineralizations, gold is represented by a silver-rich alloy, and having subordinate amounts of Cu, Bi, Ni and Mn. At Valea lui Stan the natural alloy is usually richer in Au than at Costeşti. Some compositional differences have been observed between the gold composition in respect to the host minerals. When gold is included in arsenopyrite (in both occurrences) the Ag content is higher than the case in which is included in chalcopyrite (Valea lui Stan) or pyrrhotite (Costeşti).